Carbon Monoxide (CO), Nitric Oxide, and Hydrogen Sulfide Signaling During Acute CO Poisoning - Coburn, Ronald F. (Frontiers in Pharmacology, 2022)
Major toxic effects of acute carbon monoxide (CO) poisoning result from increases in reactive oxygen species (ROS) and reactive nitrogen species (RNS) producing oxidative stress. The importance of altered nitric oxide (NO) signaling in evoking increases in RNS during CO poisoning has been established. Although there is extensive literature describing NO and hydrogen sulfide (H2S) signaling in different types of cells under normal conditions, how CO poisoning-evoked deregulation of additional NO signaling pathways and H2S signaling pathways could result in cell injury has not been previously considered in detail. The goal of this article was to do this. The approach was to use published data to describe signaling pathways driven by CO bonding to different ferroproteins and then to collate data that describe NO and H2S signaling pathways that could interact with CO signaling pathways and be important during CO poisoning. Arteriolar smooth muscle cells—endothelial cells located in the coronary and some cerebral circulations—were used as a model to illustrate major signaling pathways driven by CO bonding to different ferroproteins. The results were consistent with the concept that multiple deregulated and interacting NO and H2S signaling pathways can be involved in producing cell injury evoked during acute CO poisoning and that these pathways interact with CO signaling pathways.